Image Location for Screw Dislocation—A New Point of View. (25th March 2010) - Chen Chen, Jeng-Tzong Jeng-Tzong; Lee Lee, Ying-Te Ying-Te; Chou Chou, Ke-Hsun Ke-Hsun; Lee Lee, Jia-Wei Jia-Wei
Abstract : An infinite plane problem with a circular boundary under the screw dislocation is solved by using a new method. The angle-based fundamental solution for screw dislocation is expanded into degenerate kernel. Our method can explain why the image screw dislocation is required. Besides, the location of the image point can be obtained easily by using degenerate kernel after satisfying boundary conditions. Even though the image concept is required, the location of image point can be determined straightforwardly through the degenerate kernel instead of the method of reciprocal radii. Finally, two examples are demonstrated to verify the validity of the present method.